(untitled) (Asian Journal of Medical and Biological Research, 2021)
Osteoporosis is related to the decrease in bone mineral density. To diagnose osteoporosis and to assess its severity BMD measurement is a widely used method by using dual-energy X-ray absorptiometry (DEXA). BMD is an essential component of the assessment of bone quality and is utilized to assess the osteoporotic status of the bone for the prevention of osteoporotic fractures. The objective of this study was assessed to analyze the correlation between BMD with BMI and age. The study was conducted on 154 patients who performed the BMD test between the periods of January 2018 to July 2019. BMD of the lumbar spine (LS) and right femoral neck (FN) were measured using the DEXA method. In statistical analysis, the BMD status was compared according to age, gender, and BMI. Correlation among BMD, BMI, and age was analyzed with the nonparametric method (spearman rank correlation). SPSS software version 25 was used for analysis. Age showed highly significant negative correlations with all skeletal sites examined. Assessments on the T-score of FN and BMI were significantly related (p<0.05, r=0.223, positive relation). T-score of LS and BMI were positively correlated (r=0.484) and it was significant at a 95% level of significance. Both FN and LS T-score and showed a negative correlation, but it was significant. BMI and age were not significantly associated (p>0.05, r=-0.080, negative relation). As expected, the FN T-score and LS T-score showed a high correlation (r=0.484) between each other, and they were positive. Significant correlations were observed among BMD, BMI, and age of the patients. To identify the cause of osteoporosis, BMI and patients age can be considered as risk factors during BMD study. Our hope is that future research will reveal osteoporosis prevention targets effective for the growing population of aging men and women. Asian J. Med. Biol. Res. March 2021, 7(1): 76-81